PENGARUH PERUBAHAN SUDUT GANTRY TERHADAP NOISE PADA PEMERIKSAAN CT SCAN DENGAN TEKNIK SEQUENCE - Afif Akhsani; Luthfi Rusyadi; Fatimah (Perhimpunan Radiografer Indonesia (PARI), 2019)
Background: Noise is a fluctuation in the value of CT number and Standard Deviation which is one parameter in the assessment of CT Scan image quality. This study aims to see the effect of changes in the angle of the gantry on noise and conformity with the BAPETEN standard of the value of the CT Number and Standard Deviation fluctuations produced. Methods: This type of research is quantitative with an experimental approach. The research subjects used water phantom to assess the value of CT Number and Standard Deviation by placing ROI on the resulting image. The SPSS test is used to see the relationship between changes in noise and noise. CT Number, Uniformity and Noise Uniformity tests are performed to assess CT Number and Standard Deviation in accordance with BAPETEN regulations. Results: An increase in noise is indicated by fluctuations in the value of CT Number and Standard Deviation resulting from the placement of the ROI at the center of each image produced by each change in the angle of the gantry. The average value of CT Number at the gantry angle 00 (-1.43), 50 (-1.48), 100 (-1.47), 150 (-1.58), 200 (-1.62), 250 (-1.68), 300 (-1.7). The average value of the Standard Deviation at the 00 gantry angle (2.36), 50 (2.35), 100 (2,3), 150 (2,33), 200 (2,42), 250 (2,57), 300 (2.62). There is a significant relationship to the Pearson correlation test between changes in gantry angle and CT Number and Standard Deviation values. CT Number, Uniformity, and Noise Uniformity Test results were used to assess the fluctuations of CT Number and Standard Deviation due to changes in the angle of the gantry in accordance with the standard BAPETEN No. 2 of 2018 on all changes in the 00 gantry angle to -300 with a range of 50. Conclution:. Noise fluctuations are caused by changes in the thickness of the scanning area object from changes in the gantry angle. The greater the change in angle of the gantry, the greater the thickness of the scanning area object. Changing the gantry angle causes the scanning area to change from the circle to the ellipse.